New insight to the use of oyster shell for removing phosphorus from aqueous solutions and fertilizing rice growth - Lee, Jae In; Kang, Jin Kyu; Oh, Jung Seok; Yoo, Soo Cheul; Lee, Chang Gu; Jho, Eun Hea; Park, Seong Jik (Journal of Cleaner Production, 2021)
The excess amount of phosphorus (P) in water bodies can cause eutrophication, while the lack of P in soil can limit plant growth. Therefore, this study proposes to recover P from eutrophic lakes and use the recovered P as a fertilizer for rice growth in soil. In order to recover P from water bodies, oyster shell wastes (OySh) were used to prepare an adsorbent for P removal. The P-adsorbed adsorbent can then be used as fertilizer to release P to the soil slowly. This study investigates the feasibility of the OySh as both the P adsorbent and fertilizer, and involves four major experiments: the characterization of the OySh, adsorption experiments, toxicity tests, and pot experiments for rice growth. The OySh was thermally treated to improve its adsorption capacity for P, and the OySh calcined at 800 °C (OySh-800) showed noticeably high P adsorption. The P adsorption to the OySh-800 was quantified in batch experiments under various conditions and column experiments using natural lake water. The potential use of P adsorbed OySh-800 (P-OySh-800) as a P fertilizer was assessed by its toxicity test using bioluminescent bacteria and earthworms and pot experiments for rice growth. X-ray diffraction and X-ray photoelectron spectroscopy analyses revealed that P adsorption by the OySh-800 was achieved by the reaction between P and the calcium in the OySh-800, which formed Ca(PO3)2 and Ca4.885(PO4)3(OH)0.654. The P adsorption on the OySh-800 took 72 h to reach the equilibrium, and the maximum P adsorption capacity was 228.15 mg/g, which was higher than that of other adsorbents used for P removal. In the column experiment, a breakthrough point was reached in 20 h, and 73.6% of the P in the lake water was removed. The toxic effects of the OySh-800 determined by Allivibrio fischeri (EC50 of 896 mg/L) decreased after P adsorption (EC50 of 28 300 mg/L for P-OySh-800). When the OySh-800 and P-OySh-800 were applied at 0%–0.42% in soil, the toxic effects of both adsorbents on earthworms were negligible. The application of the P-OySh-800 at the medium level (i.e., 0.1 g/kg-soil) significantly promoted rice growth (i.e., increased tiller number). The application of organic wastes (i.e., OySh-800) as value-added materials to remove P from water and subsequently supply P for rice cultivation can address two environmental issues with P, excess of P in water bodies causing eutrophication and lack of P in the soil.
Keywords: Adsorption capacities; Column experiments; Oyster shell; P removal; Phosphorus removal; Plant growth; Pot experiment; Rice growths; Toxicity test; Waterbodies; Fertilizer; oyster Shell; Phosphorus removal; Plant growth; Toxicity